Naididae (Clitellata : Oligochaeta) and Aeolosomatidae ( Polychaeta : Aphanoneura) Species associated with aquatic plants in Tigris River/ Baghdad / Iraq (Baghdad Science Journal, 2013)
339 individuals , were sorted from 22 samples collected from three sites in Tigris River including , Al- Sarafiya district (S1), Al- Jaderiyah district (S2) and Al-Za'afaraniya district (S3), in addition to one site in the irrigation canal of the Al- Jaderiyah campus of the University of Baghdad (S4) , and in Al- Jeish canal(S5) east Baghdad. The sorting results revealed that the highest number of individuals of 102 was recorded at S4, whereas the lowest number of 24 individuals was recorded at S2. Regarding the sites, site S4 was the richest site with 30% of the total number represented 16 species, while each of S3 and S5 had 8 species only with 17.11% and 28.60% of the total individuals number respectively. The values of Jaccared Similarity Index, shows that the highest similarity index of 81% was recorded between S2 & S4.Sorted Naididae worms comprised, 17 species of the subfamily Naidinae with 59% of the total number ,10 species of them are new record to Iraq, and 6 species are new records to Tigris River. Four species of the Subfamily Pristininae were identified, with a percentage of 25% of the total number, two of them are new record to Iraq, while the other two are new records to Tigris River, in addition to two species of Aeolostomatidae (Aphanoneura: Polychaeta), with16% of the total number , both of them are new records to Iraq. Nine genera were recorded , from which Nais was the most abundant genus, followed by genus Pristina. These two genera were found in all study sites. Four species of Chaetogaster were observed including, C. cristallinus; C. diastrophus; C.Limnaei and C. langi, The first two species are new record to Iraq , and they are the most abundant species within the Chaetogaster collections . Uncinais minor, Slavina appendiculata and Allonais inaequalis were three species new record to Iraq. The first species was found in S5 and, second species in S1 , while the third one was found in S1& S5 . Three species of Dero were identified, including, D.dorsalis, D. obtusa and D. digitata, the first two species are new record to Iraq , and the last one is new record to Tigris RiverTwo species of Stylaria were observed including, S. lacustris and S. fossularis. Latter species was new record to Tigris River.Regarding the genus Nais, five species were recorded, including Nais varaibilis; N . comminus; N. simplex; N. paradalis and N. elinguis; The first three species are new record to Iraq, while the last two species are new record to Tigris River.According to subfamily Pristininae, Four species of Pristina were identified, P.aequiseta, P.longiseta , P. Proboscidea , and P. foreli. The first two species were the most abundant species of Pristina . P. foreli is new record to Iraq, while the other three species were new recods to Tigris River.Finally , a number of 55 individuals of genus Aeolosoma were recorded in S5 only, with two species including A. quarternarium and Aeolosoma leidyi , The two species are new record to Iraq.According to above results, it is clear that there were 14 & 8 species new records for Iraq and Tigris River in this investigation respectively.